Hubungan antara Radio Streaming dengan Persepsi dan Kepuasan Audiens di PT MNC Skyvision Jakarta - Rocky Prasetyo Jati; Mira Herlina (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2013)
This research is motivated by development of radio broadcasting using streaming concept to broadcast to the listeners. Before streaming broadcast radio it need planting perception, resulting satisfaction to listeners. Problem and research objectives is to what extent the relationship between the audience’s perception of streaming radio and streaming radio contact with the extent of audience satisfaction. This research based on the theory of use and gratification and using the quantitative methodology, with quota sampling technique, respondents of PT. MNC Sky Vision Jakarta. The research result shown that there is a relation between the perception of streaming radio and there is a real relationship between the satisfaction of streaming radio.